Key competencies and role profiles for sports managers: a multi-dimensional analysis - Carranza Bautista, Daniel; Valcarce Torrente, Manel; Amaya Sánchez, Blanca Esneda; Rojas Núñes, Claudia Fernanda (My University, 2024)
Sports organizations, to be profitable and competitive, become structures that demand the integration of competent personnel with certain characteristics and specific attributes determined by the job profile. This position rests on the purpose of productivity through good performance to fulfill the mission, vision, policies, goals, or objectives of the organization. Preceding from the above, there is diversification regarding the competencies, attributes, elements, and operational components that a sports manager must adopt to practice their profession successfully. In this sense, the aim of this study is to determine the elements and ideal holistic components that integrate the competencies and job profiles of the sports manager in the professional context. The research methodology uses nine variables in three dimensions: one related to six levels of mastery in sports management, another that refers to competencies, and one more that focuses on the job profile, resulting in 15 specific traits that a sports manager must develop to be professionally competent. Keywords: job profile; competence; sports management; sports manager; management skills
Keywords: job profile; competence; sports management; sports manager; management skills